Physical exercise and non‐insulin glucose‐lowering therapies in the management of Type 2 diabetes mellitus: a clinical review. Issue 3 (7th December 2018) - Eckstein, M. L.; Williams, D. M.; O'Neil, L. K.; Hayes, J.; Stephens, J. W.; Bracken, R. M.
Abstract: In the UK the National Institute of Health and Care Excellence (NICE) advocates intensive lifestyle programmes that attain the levels of daily physical activity set out by the Chief Medical Officer as a first‐line strategy for improving the health of people at risk of developing diabetes or reducing the risk of development of Type 2 diabetes. For people with Type 2 diabetes, lifestyle measures complement pharmacological treatments that include both oral and injectable therapies. In line with this, NICE guidelines also support intensification of efforts to improve patient lifestyle along with these glucose‐lowering therapies. There is a paucity of evidence, however, in the available published literature examining the association between glucose‐lowering therapies and exercise metabolism. In the present review we explore the current knowledge with regard to the potential interactions of oral and non‐insulin injectable therapies with physical activity in people at risk of, or who have, Type 2 diabetes, and present evidence that may inform healthcare professionals of the need to monitor patients more closely in their adaptation to both pharmacological therapy and physical activity. What's new?: Independently, both lifestyle intervention programmes that encourage regular physical activity and glucose‐lowering oral or injectable therapies reduce the risk of development of Type 2 diabetes and improve glycaemia in those already with the condition. This review summarizes and consolidates available research on the observed effects of each class of oral and non‐insulin injectable diabetes medication in combination with acute or chronic physical activity in people at risk of developing or already with Type 2 diabetes. This review may help clinicians understand the possible interactions of some oral and injectable diabetes medications with physical activity.